The association between the cardiometabolic index and hyperuricemia: 2011–2016 NHANES - Zhou, Yishan; Zou, Yihong; Cao, Yuyu; Gao, Yang; Pi, Ying; Tang, Xiaona; Liu, Yang; Zhong, Yanghong (Frontiers in Endocrinology, 2025)
BackgroundCentral obesity is associated with hyperuricemia. However, the association between the cardiometabolic index (CMI), which incorporates abdominal obesity and lipid metabolism parameters to assess central obesity, and hyperuricemia, is unclear. This study aimed to explore the association between CMI and hyperuricemia.MethodsWe enrolled 5,338 study participants from the 2011–2016 National Health and Nutrition Examination Survey. The participants were divided into three groups based on tertiles of CMI. We performed linear regression and employed weighted logistic regression models, subgroup analyses, and restricted cubic spline (RCS) regression to investigate the association between CMI and hyperuricemia.ResultsIn this study, 20.4% of the participants were diagnosed with hyperuricemia. A higher CMI correlated consistently with increased serum uric acid levels (β: 0.51; 95% confidence interval (CI): 0.38–0.64) and hyperuricemia (odds ratio (OR): 2.62; 95% CI: 1.91–3.61). In the fully corrected model, for each unit increase in CMI, the incidence of hyperuricemia increased by 54% and serum uric acid levels increased by 0.28 mg/dL. Subgroup analyses showed that the association of CMI with hyperuricemia was stably present in all subgroups. Interaction effects were observed for sex and body mass index subgroup (p for interaction: < 0.05). RCS regression highlighted a significant positive nonlinear association (p < 0.001).ConclusionOur results indicated a significant positive association between CMI levels and hyperuricemia risk among US adults.